Valuing local humanitarian knowledge: learning from the Central African Republic - Piquard, B; Delft, L (Refugee Studies Centre, University of Oxford, 2018)
The humanitarian community needs to better identify, collect, harness and disseminate the local humanitarian knowledge that is developed within protracted conflict settings by national NGOs.